2013
DOI: 10.1007/s11552-013-9529-2
|View full text |Cite
|
Sign up to set email alerts
|

Disability and Pain after Cortisone versus Placebo Injection for Trapeziometacarpal Arthrosis and De Quervain Syndrome

Abstract: Background This study tested the null hypothesis that type of injection (corticosteroid vs. placebo) is not a predictor of arm-specific disability as measured with the Disabilities of Arm, Shoulder and Hand questionnaire 1 to 3 months after injection of dexamethasone or placebo for treatment of trapeziometacarpal (TMC) arthrosis or de Quervain syndrome. Secondly, we tested if type of injection was a predictor of pain intensity. Methods Thirty-six English-speaking adults with TMC arthrosis or de Quervain syndro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 21 publications
0
29
0
Order By: Relevance
“…93;110 Longitudinal studies show associations of catastrophizing with worsening pain and reduced treatment benefit among, for example, arthritis patients recovering from knee surgery. 60;70;195;238 Multiple randomized controlled trials have shown that pain patients with high pre-treatment catastrophizing scores report less benefit from topical analgesics 151 , cortisone 150 , oral analgesics 200 , pain-relieving surgeries 238 , and psychosocial treatments such as CBT. 53;232 …”
Section: Psychosocial Factors Influencing Pain-related Outcomesmentioning
confidence: 99%
“…93;110 Longitudinal studies show associations of catastrophizing with worsening pain and reduced treatment benefit among, for example, arthritis patients recovering from knee surgery. 60;70;195;238 Multiple randomized controlled trials have shown that pain patients with high pre-treatment catastrophizing scores report less benefit from topical analgesics 151 , cortisone 150 , oral analgesics 200 , pain-relieving surgeries 238 , and psychosocial treatments such as CBT. 53;232 …”
Section: Psychosocial Factors Influencing Pain-related Outcomesmentioning
confidence: 99%
“…Retrospective survey studies in patients with musculoskeletal pain have indicated that catastrophizing often emerges as one of the most important pre-treatment variables predicting surgical outcomes [154;213], and a risk factor that impairs the effectiveness of pain-relieving interventions [123;138]. Multiple RCTs in various neuropathic and musculoskeletal pain conditions have shown that pain patients with high pre-treatment catastrophizing report less benefit from topical analgesics [165], cortisone [163], an oral acetaminophen and tramadol combination [209], and psychosocial treatments such as cognitive behavioral therapy (CBT) [68;232], though few of these studies tested for treatment effect modification. A recent study of patients with persistent temporomandibular joint pain, randomized to 6 weeks of either standard care or CBT and followed for 12 months, confirmed the long-term predictive effects of catastrophizing [158].…”
Section: Phenotypic Domainsmentioning
confidence: 99%
“…Although previous studies have compared the effect of brace types on pain relief and functional outcomes in the past, none to our knowledge have investigated the relationship between disability and pain with regard to treatment [13,14]. However, there is a growing body of evidence that suggests that disability related to upper extremity musculoskeletal conditions in general and lateral epicondylitis in particular, is affected by more than pain [15][16][17]. Other factors contributing to disability may include catastrophic thinking, kinesophobia, as well as occupational and psychological stresses [15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing body of evidence that suggests disability related to musculoskeletal conditions is not only associated with pain but also by patient coping strategies, as well as kinesophobia [15][16][17]. That is, patients may develop patterns of catastrophic thinking, feelings of helplessness related to the pain and fear of its worsening, which thereby affect disease-related disability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation